2006
DOI: 10.2320/matertrans.47.1360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Vibrations on Glass-Forming Ability in Fe-Co-B-Si-Nb Bulk Metallic Glasses

Abstract: It is known that cooling rate from the liquid state is an important factor for producing the bulk metallic glasses. However, almost no other factors such as electric and/or magnetic fields were investigated. The present authors have reported that a new method for producing Mg-Cu-Y bulk metallic glasses by using electromagnetic vibrations is effective in forming the metallic glass phase. However, effects of the electromagnetic vibrations on glass-forming ability in other alloy systems are not investigated. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This result is the same as the result of XRD. It is considered that heterogeneous crystalline nuclei exist in the liquid region when heat treatment temperature is close to the solidus temperature [16][17][18][19][20][21][22][23][24]. Thus, it is presumed that heterogeneous crystalline nuclei related to unknown crystalline phase decrease the glass forming ability for the samples heat treated at low temperatures.…”
Section: Thermec 2013mentioning
confidence: 99%
“…This result is the same as the result of XRD. It is considered that heterogeneous crystalline nuclei exist in the liquid region when heat treatment temperature is close to the solidus temperature [16][17][18][19][20][21][22][23][24]. Thus, it is presumed that heterogeneous crystalline nuclei related to unknown crystalline phase decrease the glass forming ability for the samples heat treated at low temperatures.…”
Section: Thermec 2013mentioning
confidence: 99%
“…However, this increase in the cooling rate disappears with electromagnetic vibrational frequencies of more than 10 kHz. [15][16][17] It was found that the absence of macroscopic stirring resulted in the disappearance of the increase in the cooling rate because of the nanometer-sized amplitudes at higher frequencies. When particles in the liquid metal have lower electric resistance than the liquid metal, these particles are considered to vibrate vigorously in the liquid metal by Lorentz force, because the electric current concentrates in those.…”
Section: Introductionmentioning
confidence: 97%
“…The second effect is the decrease in the number of crystal nuclei. [12][13][14] If it is supposed that only the alloy sample exists in the free space and that the electric current is passed through the sample uniformly, the electromagnetic vibrations are the vibrating motion and not waves like the ultrasonic waves. However, when particles in the sample have lower electric resistance than the molten sample, these particles are considered to vibrate vigorously in the molten sample by Lorentz force because the electric current concentrates in those.…”
Section: Introductionmentioning
confidence: 99%